PENGARUH PEMAHAMAN DIGITALISASI SISTEM ADMINISTRASI PAJAK DAN DIGITAL TRANSFORMASI TERHADAP KEPATUHAN PAJAK NON-KARYAWAN - Brenda Ernsky Palar; Riky Sai Maruli; Hisar Pangaribuan (JURNAL LENTERA BISNIS, 2024)
Tax compliance is crucial for sustainable economic development and fiscal stability. This study explores the impact of understanding digitalization of tax administration systems on digital transformation and tax compliance. Using a quantitative approach, data were collected through an online questionnaire distributed to 100 graduates from the Faculty of Economics at Universitas Advent Indonesia, selected via random sampling. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that understanding digitalization of tax administration systems has a positive and significant effect on digital transformation, supporting strategic changes in business management through technology. Additionally, understanding digitalization of tax administration systems significantly affects tax compliance; the better the understanding, the higher the tax compliance. However, digital transformation does not significantly impact tax compliance, and understanding digitalization of tax administration systems through digital transformation does not significantly affect tax compliance. These findings suggest that enhancing tax compliance requires a comprehensive approach including regulation, awareness, and taxpayer motivation, alongside leveraging digitalization to improve tax administration efficiency.